2020
DOI: 10.1007/s42991-020-00052-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of activity rhythms of invasive coypus Myocastor coypus inferred through camera-trapping

Abstract: Studies on activity rhythms are pivotal for the management of invasive alien species, as they provide basic insights into species basic ecology and may increase the success of control programs. The coypu Myocastor coypus, introduced from South America for fur farms, has become one of the most invasive rodents in Europe. Introduced coypus may affect crop productions, as well as natural vegetation and the breeding success of wading birds. In this study, we examined activity data collected through intensive camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…Therefore, activity patterns need to be considered in different environmental contexts (e.g. Ashby 1972;Kerr 1997;Jordan et al 2007;Brivio et al 2017;Mori et al 2020a). The European wildcat is fully protected over most of its range, under national and international legislations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, activity patterns need to be considered in different environmental contexts (e.g. Ashby 1972;Kerr 1997;Jordan et al 2007;Brivio et al 2017;Mori et al 2020a). The European wildcat is fully protected over most of its range, under national and international legislations.…”
Section: Introductionmentioning
confidence: 99%
“…Camera trapping is being increasingly employed to estimate animal distribution and abundance, as well as local species richness (Tobler et al 2008;O'Connell et al 2011;Borchers et al 2014;Kikuchi et al 2020). This represents a reliable method to assess the temporal behaviour of animal species (Leuchtenberger et al 2014;Mori et al 2020a;Rossa et al 2021). Activity rhythms of the wild cat can hardly be directly estimated by direct observations, as being nocturnal and elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The use of camera-traps has provided important ecological information concerning the spatiotemporal behavior of wild species, including species of conservation interest [ 4 ], rare/elusive species [ 5 , 6 , 7 ], as well as problematic species requiring management action such as alien species [ 8 , 9 ]. It has been shown that 30–100 independent camera-trap records per species for each season or year may be sufficient to estimate activity rhythms of wildlife, with results comparable to those obtained from GPS or radio-tracked animals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These patterns of activity not only vary among species (Gómez et al 2005;Caravaggi et al 2018;Vazquez et al 2019;Mori et al 2021) but vary across latitudes and seasons (Ikeda et al 2016). Many factors can influence activity, such as competition (Rychlik 2005), predator-prey relationships (Mori et al 2020), temperature (Hanya et al 2018), resource availability (Pereira 2010), moonlight (Huck et al 2017) and precipitation (Suzuki and Ando 2019). In addition, individuals within species may also show different patterns of activity rhythms in response to different environmental conditions (Hertel et al 2017).…”
Section: Introductionmentioning
confidence: 99%